Health care professionals' conceptions of respiratory symptoms and physical activity in patients with acute pulmonary embolism. A phenomenographic interview study. Issue 212 (April 2022) - Danielsbacka, Jenny S.; Mannerkorpi, Kaisa; Olsén, Monika Fagevik
Abstract: Introduction: Acute pulmonary embolism (PE) often presents with respiratory symptoms, such as dyspnea and respiratory pain, and patients are affected both physically and mentally by the consequences of PE for a long time after the event. This study aimed to explore health care professionals (HCPs) conceptions of respiratory symptoms, physical activity, and information given to patients during in-hospital care. Materials and methods: Qualitative individual interviews were conducted with twenty-one HCPs (physicians, nurses, physiotherapist) working with patients with PE, and analyzed with a phenomenographic approach. Results: The findings resulted in an overall theme: "Health care professionals' knowledge of PE, and an individualized patient approach, are cornerstones for adequate management of respiratory symptoms in PE". Three major categories described conceptions of a heterogenous patient group physically and mentally affected by their respiratory symptoms, of accurate information given at right time being crucial, and of giving appropriate information about respiratory symptoms and physical activity being complex due to many prerequisites needing to be fulfilled. Conclusions: This study provides new knowledge about the complexity of management of patients with PE and respiratory symptoms. The patient group was conceived as heterogenous with different needs for information given at the appropriate time. Structural prerequisites, such as time and staff rotation in the hospital setting, and personal issues, for example levels of knowledge of PE among HCPs affected the ability of HCPs to give correct information. Further research is needed to ensure optimal design of in-hospital care for patients with PE. Highlights: Management of patients with pulmonary embolism and respiratory symptoms is complex. The patient group was conceived as heterogenous with different information needs. Information of physical activity needs to be given early during in-hospital care. Structural prerequisites affect the ability to give correct information.